Abduction and Semiosis - Rodrigues, Mariana Vitti [UNESP] (Springer Nature, 2023)
This chapter presents the concept of abduction in the context of Peircean General Theory of Signs or Semiotics. It introduces the role of abduction, understood as a hypothesis-making reasoning, in the dynamic, collective, and meaning-making process of sign action, or semiosis. In general terms, abduction can be described as an ampliative form of argument which starts from a surprising fact, something unexpected, some state of doubt or curiosity and concludes provisionally with a reasonable hypothesis that is worth of further investigation. It describes the semiotic structure of abduction by highlighting the role of iconicity in the elaboration of possible imaginary scenarios by the unveiling of clue-like signs in order to conceive plausible explanations about the object under investigation. Illustrative examples of abduction, in science and daily life, are given to aid the understanding of the semiotic nature of abductive reasoning.
Keywords: Abduction; Making processes; Meaning; Pragmaticism; Scientific discovery; Semiosis